NEMA NU 4-2008 and in vivo imaging performance of RAYCAN trans-PET/CT X5 small animal imaging system. (29th May 2019) - Teuho, J; Han, C; Riehakainen, L; Honkaniemi, A; Tirri, M; Liljenbäck, H; Virta, J; Gu, S; Liu, S; Wan, L; Teräs, M; Roivainen, A; et al.
Abstract: The RAYCAN Trans-PET/CT X5 is a preclinical positron emission tomography and computed tomography (PET/CT) system intended for in vivo imaging of rats and mice, featuring all-digital readout electronics for PET data acquisition. The National Electrical Manufacturers Association (NEMA) NU 4-2008 performance evaluation was conducted on the RAYCAN Trans-PET/CT X5 in addition to assessing in vivo imaging performance of the system on live animals. The performance characteristics of the system were evaluated, including system spatial resolution, count rate performance, sensitivity and image quality. The system imaging performance is assessed in dynamic in vivo PET imaging. The system resolution defined as full width half maximum (FWHM) was 2.07 mm, 2.11 mm and 1.31 mm for the tangential, radial and axial resolution, respectively, at the center of the field of view. The peak noise equivalent count rate (NECR) values measured were 61 kcps at 0.19 MBq ml −1 for the rat size phantom and 126 kcps at 1.53 MBq ml −1 for the mouse size phantom. Scatter fractions were 24% and 14% for the rat and mouse phantom. The measured peak sensitivity of the system was 1.70%. Image quality in static imaging was deemed sufficient based on the image quality phantom study, with average activity concentration of 155  ±  8.6 kBq ml −1 and image uniformity of 5.57% when using two-dimensional filtered backprojection algorithm (2D-FBP). Rods in the image quality phantom were visualized easily up to 2 mm in size. In dynamic in vivo PET imaging, time-activity-curves from several regions were successfully measured, characterizing the radioactivity distribution in myocardial blood pool, liver, left ventricle and the lung. In conclusion, the RAYCAN Trans-PET/CT X5 system can be considered a suitable option for basic imaging needs in preclinical imaging.